Interconnection of Religious Education and Modern Science in Islamic Religious Learning - Firman Mansir (Tarbiyah Departement collaboration with AMCA, 2021)
This study discusses the relationship between Islamic education and science at Madrasah Ibtidaiyah, an essential educational institution. Islamic religious education directed at schools, especially Madrasah Ibtidaiyah, is a procedure to enforce the basics of faith and devotion to students. Strengthening science and technology allows students to do various things to realize multiple needs in their lives. This study aims to determine the relationship between Islamic education and modern science in madrasas. This study uses a qualitative method. The data collection technique used is a literature study. The data study technique uses data reduction, presentation, and conclusion drawing. The results of this study are the integrated model is a model of integrating science and Islamic religious education (PAI) in the learning process. The existence of a link between the relationship between Islamic Religious Education and science at madrasah can provide new insights for students about the importance of science and religion in religious and social life.